The role of tumour necrosis factor alpha and soluble tumour necrosis factor alpha receptors in the symptomatology of schizophrenia. (3rd July 2016) - Turhan, Levent; Batmaz, Sedat; Kocbiyik, Sibel; Soygur, Arif Haldun
Abstract: Background Immunological mechanisms may be responsible for the development and maintenance of schizophrenia symptoms.Aim The aim of this study is to measure tumour necrosis factor-alpha (TNF-α), soluble tumour necrosis factor-alpha receptor I (sTNF-αRI), and soluble tumour necrosis factor-alpha receptor II (sTNF-αRII) levels in patients with schizophrenia and healthy individuals, and to determine their relationship with the symptoms of schizophrenia.Methods Serum TNF-α, sTNF-αRI and sTNF-αRII levels were measured. The Positive and Negative Syndrome Scale (PANSS) was administered for patients with schizophrenia (n = 35), and the results were compared with healthy controls ( n  = 30). Hierarchical regression analyses were undertaken to predict the levels of TNF-α, sTNF-αRI and sTNF-αRII.Results No significant difference was observed in TNF-α levels, but sTNF-αRI and sTNF-αRII levels were lower in patients with schizophrenia. Serum sTNF-αRI and sTNF-αRII levels were found to be negatively correlated with the negative subscale score of the PANSS, and sTNF-αRI levels were also negatively correlated with the total score of the PANSS. Smoking, gender, body mass index were not correlated with TNF-α and sTNF-α receptor levels.Conclusions These results suggest that there may be a change in anti-inflammatory response in patients with schizophrenia due to sTNF-αRI and sTNF-αRII levels. The study also supports low levels of TNF activity in schizophrenia patients with negative symptoms.